Tuesday, December 12

The Elimination Method of Solving Simultaneous Equations (5 Easy Steps)

Google+ Pinterest LinkedIn Tumblr +

If you are asked to solve a pair of simultaneous equations what you need to do is find the values of x and y which satisfy both equations. There are two methods that you can use to solve simultaneous equations – substitution method or elimination method. In this article we shall be solving the simultaneous equations by elimination.

To solve simultaneous equations by elimination follow these simple steps:

Step 1 Make the coefficients of x (or y) the same in both equations by multiplying the equations. Sometimes only 1 equation may need to be multiplied to make the coefficients the same. Or in easier examples the coefficients of x (or y) may already be the same in both equations so this step can be left out.

Note: A coefficient is the number before the letter.

Step 2 Once the coefficients are the same take the two equations away.

Step 3 After step 2 one of the variables will be eliminated, so solve the equation that is left to find the value of the first letter.

Step 4 Find the value of the other variable (letter) by substituting your answer  from step 3 back into the first equation.  

Step 5 Now you have found both values, substitute the values back into the second equation to check that they work.

Let’s take a look at an example:

Example 1

Solve this pair of simultaneous equations by using elimination:

3x + 5y = 27         (1)

9x + 2y = 42         (2)

Step 1:

Let’s make the x coefficients the same. Do this by multiplying the first equation by 3, and leaving the second equation unchanged.

9x + 15y = 81      (3)

9x + 2y = 42         (4)

(Notice all the numbers are multiplied by 3)

Step 2:

Take the two equations away.

13y = 39               

Step 3:

Solve this equation:

13y = 39                (÷3)

y = 3

Step 4:

Now substitute y = 3 into the first equation to find the value of x.

3x + 5y = 27         (1)

3x + 5×3 = 27

3x + 15 = 27         (-15)

3x = 12                  (÷3)

x = 4

Step 5:

Since we now know that x = 4 and y = 3, check that these values work in the second equation to confirm they are correct.

9x + 2y = 42         (2)

9 × 4 + 2 × 3 = 42

36 + 6 = 42

42 = 42

Since both sides are equal we know our two variables are correct.

For some more examples on solving by elimination click here.

For some harder examples click here.

Share.

About Author

Leave A Reply